Design Of A Broadband Microstrip Array Antenna For 5G Application - Alwareth, Husam; Abu, Maisarah; Mohd Ibrahim, Imran (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
This paper presented a study that analyses the enhancement of high gain microstrip array antenna for 5G applications operating at 28 GHz designed to meet the ETSI standardization. It is expected that the gain must be high at high operating frequency so that it can compensate the propagation path loss. The objective of this study was to design a 16-element microstrip array antenna located at the top of antenna as a rectangular patch. Aiming to achieve low loss and high antenna efficiency, the material used for the proposed design was Roger 5880 materials with the permittivity of 2.2 and thickness of 0.25. Initially, a rectangular microstrip array antenna with 4 elements was designed. After analyzing the outcomes of antenna features such as reflected loss, efficiency and antenna gain, the 4 elements array were transformed into 8 elements array. To achieve high gain, it was then transformed into 16 elements array. Based on EM analysis using CST software, it was found that the proposed antenna has high efficiencies and high gain of 18.5 at 28 GHz operating frequency.